The Burden of Cerebral Venous Thrombosis in a Romanian Population across a 5-Year Period - Adina Stan; Silvina Ilut; Hanna Maria Dragos; Claudia Bota; Patricia Nicoleta Hanghicel; Alexander Cristian; Irina Vlad; Diana Mocanu; Stefan Strilciuc; Paul Stefan Panaitescu; Horatiu Stan; Dafin F. Muresanu (Life, 2022)
Health policies in transitioning health systems are rarely informed by the social burden and the incidence shifts in disease epidemiology. Cerebral venous thrombosis (CVT) is a type of stroke more often affecting younger adults and women, with higher incidences being reported in recent studies. A retrospective, hospital-based population study was conducted at Cluj-Napoca Emergency County Hospital across a 5-year period between 2017 and 2021. The overall incidence and the rates in distinctive gender and age groups were assessed. Length of hospital stay (LHS), modified Rankin score (mRS) and mortality at discharge and at 3 months were calculated. Fifty-three patients were included. The median age was 45 years, and 64.2% were women. In our population of 3,043,998 person-years, 53 CVT cases resulted in an incidence of 1.74 per 100,000 (95% CI 1.30–2.27). CVT incidence was higher in women (2.13 per 100,000, 95% CI 1.47–2.07). There was a statistically significant difference in LHS between patients with different intracranial complications (Kruskal–Wallis, p = 0.008). The discharge mRS correlated with increasing age (rs = 0.334, p = 0.015), transient risk factors (Fisher’s exact test, p = 0.023) and intracranial complications (Fisher’s exact test, p = 0.022). In addition, the mRS at 3 months was statistically associated with increasing age (rs = 0.372, p = 0.006) and transient risk factors (Fisher’s exact test, p = 0.012). In-hospital mortality was 5.7%, and mortality at follow up was 7.5%, with higher rates in women (5.9% and 8.8%, respectively). Our findings may provide insight regarding the epidemiological features of certain patient groups more prone to developing CVT and its complications, informing local and central stakeholders’ efforts to improve standards of care.